The family business: Is there a future for small farms? - Fritschel, Heidi (International Food Policy Research Institute, 2014)
The United Nations declared 2014 the International Year of Family Farming. Although many forms of production were once family-based, agriculture is now one of the few that are still dominated by families. Because family farms are so prevalent, making them more productive could help combat poverty and hunger in many rural areas around the world. Family farms are mostly small in scale, but they are highly diverse in other ways, and their pathways out of poverty will vary. The feature article in this issue of Insights looks at the prospects for supporting family farmers and, in some cases, encouraging workers to move off of farms in favor of other opportunities.